Citizenship studies - Mitchell, Mike (Hodder Education, 2021)
Encourage students to take an active role in citizenship with fully updated content that will allow them to understand the key issues and concepts they need to know using clear, detailed explanations of key terms, supported by real-life case studies that will bring the topic to life. This book contains: - Extensive coverage of tricky topics so students can avoid common mistakes - Up-to-date case studies covering all recent developments relevant to the course - Activities and discussion points, review questions and learning points that teach students the research, analytical, interpretative and evaluative skills required - Fully revised exam-style questions throughout the book, as well as assessment guidance and useful advice on writing exam answers - Links to relevant websites to allow further subject enrichment.